Contemporary 3D planning for distraction osteogenesis creating predictable outcomes - Rachael Suffern; Salim Miskry; Jonas Osher (Elsevier, 2021)
Distraction osteogenesis is a treatment option for severely hypoplastic jaws meaning large distance jaw repositioning can occur without the need for 'staged' osteotomies. We propose utilising a hybrid approach of three-dimensional virtual planning combined with stock distractors as a novel way of reducing operative time and creating predictable outcomes. The distraction is digitally planned to give the ideal position of the distractors and correct vector of distraction. A stereolithic model is fabricated and used to bend the stock distractor plates pre-operatively to ensure good adaptation, with minimal bending required intra-operatively. A custom bite jig positions the distractors and ensures that the vector is as planned. Stock distraction plates are time consuming and challenging to adapt intra-operatively, hence the ability to move this stage of the operation out of theatre reduces the operative time and allows accurate, aesthetic results.